Capsaicin-evoked CGRP release from rat buccal mucosa: development of a model system for studying trigeminal mechanisms of neurogenic inflammation - Flores, Christopher M.; Leong, Anthony S.; O. Dussor, Gregory; Hargreaves, Kenneth M.; Kilo, Sonja (The European journal of neuroscience, 2001)
Many of the physiological hallmarks associated with neurogenic inflammatory processes in cutaneous tissues are similarly present within orofacial structures. Such attributes include the dependence upon capsaicin‐sensitive sensory neurons and the involvement of certain inflammatory mediators derived therein, including calcitonin gene‐related peptide (CGRP). However, there are also important differences between the trigeminal and spinal nervous systems, and the potential contributions of neurogenic processes to inflammatory disease within the trigeminal system have yet to be fully elucidated. We present here a model system that affords the ability to study mechanisms regulating the efferent functions of peptidergic terminals that may subserve neurogenic inflammation within the oral cavity. Freshly dissected buccal mucosa tissue from adult, male, Sprague–Dawley rats was placed into chambers and superfused with oxygenated, Krebs buffer. Serial aliquots of the egressing superfusate were acquired and analysed by radioimmunoassay for immunoreactive CGRP (iCGRP). Addition of the selective excitotoxin, capsaicin (10–300 µm), to the superfusion buffer resulted in a significant, concentration‐dependent increase in superfusate levels of iCGRP. Similarly, release of iCGRP from the buccal mucosa could also be evoked by a depolarizing concentration of potassium chloride (50 mm) or by the calcium ionophore A23187 (1 µm). The specific, capsaicin receptor antagonist, capsazepine (300 µm), completely abolished the capsaicin‐evoked release of iCGRP while having no effect whatsoever on the potassium‐evoked release. Moreover, capsaicin‐evoked release was dependent upon the presence of extracellular calcium ions and was significantly, though incompletely, attenuated by neonatal capsaicin denervation. Collectively, these data indicate that the evoked neurosecretion of iCGRP in response to capsaicin occurs via a vanilloid receptor‐mediated, exocytotic mechanism. The model system described here should greatly facilitate future investigations designed to identify and characterize the stimuli that regulate the release of CGRP or other neurosecretory substances in isolated tissues. This system may also be used to elucidate the role of these mediators in the aetiology of inflammatory processes within the trigeminal field of innervation.